Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species - Kolyada, Victor; Mostovski, Mike B. (Zootaxa, 2017)
Revision of the genus Hormoserphus Townes, 1981 has shown that its type species, Proctotrupes clypeatus Ashmead, 1893 belongs to Oxyserphus Masner, 1961 (Oxyserphus clypeatus (Ashmead, 1893), comb. n. [= Hormoserphus transgressus Townes, 1981, syn. n.]) thus making Hormoserphus a junior synonym of the latter genus. Trachyserphus Kolyada, gen. n. is described to accommodate Oriental Trachyserphus segregatus (Townes, 1981), comb. n. (from Hormoserphus), Central American Trachyserphus defrictus (Townes, 1981), comb. n. (from Sminthoserphus Townes, 1981) and South American Trachyserphus masneri Kolyada, sp. n. Hormoserphus chinensis He & Fan, 1991 and Hormoserphus striatus He & Xu, 2015 are treated as junior synonyms of T. segregatus. An identification key to the species of Trachyserphus is provided.